2010
DOI: 10.1080/09540121003758606
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevention through sport: the case of the Mathare Youth Sport Association in Kenya

Abstract: Sport has become a popular tool for HIV prevention, based on claims that it can foster life skills that are necessary to translate knowledge, attitudes and behavioural intentions into actual behaviour. Empirical evidence of the effectiveness of sport-based HIV prevention programmes is, however, sorely lacking. We therefore conducted a cross-sectional survey assessing sexual behaviour and the determinants thereof among 454 youth of the Mathare Youth Sport Association (MYSA) in Kenya and a control group of 318 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…Kaufman and Welsch (2012) have examined the evidence to show the effectiveness of HIV/AIDS awareness activities through sport and found it limited. There were two quasi-experimental studies on sports-based HIV/AIDS awareness programs in Zimbabwe (Clark, Friedrich, Ndlovu, Neilands, & McFarland, 2006) and Tanzania (Maro, Roberts, & Sørensen, 2009), and a cross-sectional study in Kenya (Delva et al, 2010). Although there have been more reports based on qualitative methods such as field observations and interviews recently, it is difficult to see clear evidence of the positive role of sport or to obtain data showing the unique characteristic of sport.…”
Section: Hiv/aids Awareness and Sport In Recent Yearsmentioning
confidence: 99%
“…Kaufman and Welsch (2012) have examined the evidence to show the effectiveness of HIV/AIDS awareness activities through sport and found it limited. There were two quasi-experimental studies on sports-based HIV/AIDS awareness programs in Zimbabwe (Clark, Friedrich, Ndlovu, Neilands, & McFarland, 2006) and Tanzania (Maro, Roberts, & Sørensen, 2009), and a cross-sectional study in Kenya (Delva et al, 2010). Although there have been more reports based on qualitative methods such as field observations and interviews recently, it is difficult to see clear evidence of the positive role of sport or to obtain data showing the unique characteristic of sport.…”
Section: Hiv/aids Awareness and Sport In Recent Yearsmentioning
confidence: 99%
“…SDP projects can be implemented in many different places and situations: from short-term emergency humanitarian aid activities (like for example after a natural disaster or a conflict), where sport and play activities can provide psychosocial support to children (Henley, 2005), or in long-term development projects (like for example in a refugee camp or within an assistance program for street children) (SDPIWG, 2007a). Well structured sport initiatives can foster changes in the behavior of the people, helping them to become aware about how to engage in healthy life choices and how to prevent infections such as malaria or sexually transmitted diseases (SDPIWG, 2007a;Delva, 2010). Participation in sport is often used as a powerful tool of inclusion for persons with disabilities.…”
Section: The Contribution Of Sportmentioning
confidence: 99%
“…The researchers found that MYSA members were more likely than non-MYSA members to use condoms during the first sex act. MYSA participants also scored higher (23.2%) for consistent condom use with the current/last partner versus 17.2% among the non-member group (Delva et al, 2011). The results illustrated no significant differences between MYSA and non-MYSA members concerning their attitudes toward risk avoidance, subjective beliefs on virginity and responsibility, and behavioral intentions regarding using a condom and faithfulness to a partner.…”
Section: Sport and Healthmentioning
confidence: 75%
“…analyzed (Delva et al, 2011). The researchers found that MYSA members were more likely than non-MYSA members to use condoms during the first sex act.…”
Section: Sport and Healthmentioning
confidence: 99%